Keterkaitan Status Gizi Dengan Kejadian Phlebitis Pada Pasien Dewasa Di Ruang Flamboyan RSUD Gambiran Kota Kediri - Budi Hartanto; Moh Alimansur (Akademi Keperawatan Dharma Husada Kediri, 2014)
Phlebitis is inflammation of the vein wall due to intravenous fluid therapy, which is characterized by pain, redness, palpable soft, swollen and warm to the location of the stabbing (Prastika, 2011). Plebitis as one form of nosocomial infection is still a serious problem faced by hospitals throughout the world, especially hospitals in developing countries (Ministry of Health, 2008). The study design used by researchers is the correlation, this surveys or research that attempts to explore how and why the health phenomena occur. The population in this study are all adult patients in hospitals Gambiran Flamboyan Room Kediri in May. Sampling technique, which is used in this study is the probability sampling which simple random sampling method. Data already collected was processed and identified, then analyzed analytically using logistic regression test. Results of the study appear no link nutritional status in adult patients with phlebitis incidence (p=0.604> 0.05). The risk of the occurrence of phlebitis is caused by chemical factors, mechanical factors and infection. Keywords: Nutrition, Plebitis, infection